Perkembangan Orientalisme dan Oksidentalisme - Muzakkir; Syamsudhuha Saleh; Bahaking Rama (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the development of Orientalism and Occidentalism within the context of East–West relations and their implications for Islamic studies. This research employs a qualitative approach using library research methods, incorporating historical, philosophical, and discourse analyses. The findings indicate that Orientalism evolved from theological and colonial interests into a systematic academic discipline, yet it still contains ideological dimensions in its representation of Islam. Occidentalism emerged as an epistemological response to Western dominance and seeks to establish intellectual equality between the East and the West. The relationship between the two is dialectical, not merely confrontational but also dialogical. This study emphasizes the importance of understanding Orientalism and Occidentalism critically and proportionally within the context of globalization and contemporary Islamic studies.AbstrakPenelitian ini bertujuan untuk menganalisis perkembangan orientalisme dan oksidentalisme dalam konteks hubungan Timur dan Barat serta implikasinya terhadap studi Islam. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan melalui analisis historis, filosofis, dan wacana. Hasil penelitian menunjukkan bahwa orientalisme berkembang dari kepentingan teologis dan kolonial menjadi kajian akademik yang sistematis, namun tetap mengandung dimensi ideologis dalam merepresentasikan Islam. Oksidentalisme muncul sebagai respons epistemologis terhadap dominasi Barat dan berupaya membangun kesetaraan intelektual. Hubungan keduanya bersifat dialektis, tidak hanya konfrontatif tetapi juga dialogis. Penelitian ini menegaskan pentingnya memahami orientalisme dan oksidentalisme secara kritis dan proporsional dalam konteks globalisasi dan perkembangan studi Islam kontemporer.